On the existence of a possible A2A-D2-β- arrestin2 complex: A2A agonist modulation of D2 agonist-induced β-arrestin2 recruitment - Borroto-Escuela, Dasiel O.; Romero-Fernandez, Wilber; Tarakanov, Alexander O.; Ciruela, Francisco; Agnati, Luigi F.; Fuxe, Kjell (Sciencedirect, 2011)
Given that coactivation of adenosine A2A (A2AR) and dopamine D2 (D2R) receptors results in the coaggregation, cointernalization, and codesensitization of the A2AR and D 2R and the role of scaffolding protein β-arrestin2 in the desensitization, internalization, and signaling of G-protein-coupled receptors, in this study we explored the ability of the A2AR agonist CGS21680 in A2AR-D2R-coexpressing cells to modulate the D 2R agonist-induced recruitment of β-arrestin2 to the D 2R by means of proximity-based bioluminescence resonance energy transfer (BRET2) and co-trafficking analysis. We found evidence that CGS21680 can increase the maximal BRET2 signal between β-arrestin2RLuc and D2LRGFP2 upon D 2R activation, by increasing the potency of the D2R agonist to exert this action. In addition, this change was associated with an increased formation of cytoplasmic clusters containing β-arrestin2 GFP2 and D2LRYFP as seen from the co-trafficking analysis. Furthermore, the A2AR agonist advanced the time for the increase in Akt phosphorylation obtained with the D2R agonist. Finally, using a novel bioinformatics approach to predict the protein-protein interface, we have also found that amino acid pro-triplets TNY, LLS, RAF, and VSR may be crucial for the -induced β-arrestin2 recruitment by A2AR-D2R heteromers. Taken together, the results indicate that the antagonistic A2AR-D2R allosteric receptor-receptor interaction in A2AR-D2R heteromers favors β-arrestin2 recruitment to the D2LR protomer with subsequent cointernalization associated with a reduced time onset of Akt phosphorylation followed by a rapid dephosphorylation. Thus, β-arrestin2 action becomes more rapid and short-lasting and, in this way, mimics G-protein-mediated signaling.
Keywords: Receptores de neurotransmisores; Receptores; Dopamina - Receptores; Dopamine D2R receptor; Adenosine A2A receptor; Allosteric modulation; Signalling; Arrestin; Internalization; Oligomerization; Heteroreceptor complexes; G protein-coupled receptors